Effects of mitragynine from Mitragyna speciosa Korth leaves on working memory - Apryani, Evhy; Baharuldin, Mohamad Taufik Hidayat; Mohd Moklas, Mohamad Aris; Fakurazi, Sharida; Nasir, Farah Idayu (Elsevier, 2010)
Aim of the study: Mitragyna speciosa Korth from Rubiaceae family is a tropical plant indigenous to Southeast Asia particularly in Thailand, Peninsular of Malaysia and Indonesia. The leaves have been used by natives for their opium-like effect and cocaine-like stimulant ability to combat fatigue and enhance tolerance to hard work. However there is no scientific information about the effect of mitragynine on the cognitive performances. This study is designed to examine the working memory effects of mitragynine which is extracted from Mitragyna speciosa mature leaves.